Program Dinas Pemberdayaan Masyarakat Dan Desa Dalam Memajukan Perekonomian Desa Leubatang Di Kecamatan Omesuri Kabupaten Lembata Nusa Tenggara Timur - Siti Risdayanti Muslimin; St. Nasriah (Jurnal Berita Sosial, 2024)
This thesis discusses the Community and Village Empowerment Service Program in Advancing the Economy of Leubatang Village in Omesuri District, Lembata Regency, East Nusa Tenggara. Furthermore, the researcher elaborated into two sub-problems, namely: 1). What is the Program of the Community and Village Empowerment Office in Advancing the Economy of Leubatang Village in Omesuri District, Lembata Regency, East Nusa Tenggara? 2). What are the Inhibiting and Supporting Factors in the Implementation of the Program to Advance the Economy of Leubatang Village in Omesuri District, Lembata Regency, East Nusa Tenggara?.This type of research is qualitative descriptive which is carried out by studying in depth a problem and then the results are described. The approach method used in this study is a sociological approach. The data collection method consists of observation, interviews and documentation. Data processing techniques consist of data analysis, data reduction, and data presentation. Furthermore, the last research method used by the researcher is to draw conclusions.The results of this study show that: (1) The Program of the Community and Village Empowerment Office in Advancing the Economy of Leubatang Village in Omesuri District, Lembata Regency, East Nusa Tenggara, namely the Mutiara Village-Owned Enterprise (BumDes) called "BUMDes Mutiara". In the implementation of the BumDes program, Mutiara runs four business units consisting of a rental service business unit, a chicken farming business unit, a business unit for plantation and agricultural products, and a subsidized fertilizer procurement business unit. (2) There are factors that are inhibiting and supporting in the implementation of the BUMDes Mutiara program in increasing business units so that the inhibiting factors include limited capital, limited human resources and competition for similar services while supporting factors are demographic bonuses, dynamic village economic cycles and responsive governments.The implication of the research is that the Community and Village Empowerment Office, especially the manager of BUMDes Mutiara, pays more attention to the people of Leubatang Village, especially in terms of developing the creativity of human resources in the processing of each business unit, so that assistance is not only physical but must be accompanied by non-physical. In the implementation of the Community and Village Empowerment Office Program and the management of BUMDes Mutiara, they must provide facilities and infrastructure to make it easier for business unit actors